Dwadzieścia lat Rady Języka Polskiego: uchwały ortograficzne a polszczyzna „poprawna, dobra, etyczna i estetyczna” - Bień, Janusz S. (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The paper presents a detailed analysis of the orthographic resolutions of the Council for the Polish Language at the Presidium of the Polish Academy of Sciences, some background information is also provided. The conclusion is that the resolutions and other opinions of the Council are not formulated in the satisfactory way. Although the Council claims to support the language which is “correct, good, ethical and aesthetical”, such features are not exemplified in the texts discussed in the paper.